Galvanic cell reaction driven electrochemical doping of TiO2 nanotube photoanodes for enhanced charge separation. Issue 79 (3rd September 2018) - Zhu, Heng; Hu, Yingfei; Zhu, Kai; Yan, Shicheng; Lu, Lei; Zhao, Meiming; Fu, Hongwei; Li, Zhaosheng; Zou, Zhigang
Abstract : There is an electrochemical doping reaction that happens when TiO2 nanotube photoanodes are immersed in NaBH4 solution at room temperature. Abstract : Here, we discover that there is an electrochemical doping reaction that generates surface states when TiO2 nanotube photoanodes are immersed into NaBH4 solution, thus improving the photoelectrochemical performance due to the surface states acting as an efficient electron transfer route.